2007
DOI: 10.1111/j.1440-1746.2007.05153.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of phosphatidylcholine saturation in preventing bile salt toxicity to gastrointestinal epithelia and membranes

Abstract: Cells can show variable resistance to bile salt toxicity. Extracellular PC, especially in the unsaturated state, can directly protect cell and artificial membranes from bile salt injury. These findings support a role for biliary PC in the formation of mixed micelles that have low cytotoxic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…From the plot, it can be concluded that the cell growth inhibition between CUR inside mixed micelles and free CUR had no significant differences at the concentration range from 0.75 to 3 mg/ml and 12 to 24 mg/ml; however, great changes occurred from 3 to 12 mg/ml. Empty micelles, just containing PC and bile salt, also represented a certain cell toxicity probably owing to the toxicity of SDC to epithelia and membranes, which could be counteracted partly by PCs (Dial et al, 2008). The IC 50 values on MCF-7 cells of CUR-PC-SDC-MMs and free drug solution were 4.10 mg/ml and 6.93 mg/ml, respectively.…”
Section: Cell Toxicity Assaysmentioning
confidence: 87%
“…From the plot, it can be concluded that the cell growth inhibition between CUR inside mixed micelles and free CUR had no significant differences at the concentration range from 0.75 to 3 mg/ml and 12 to 24 mg/ml; however, great changes occurred from 3 to 12 mg/ml. Empty micelles, just containing PC and bile salt, also represented a certain cell toxicity probably owing to the toxicity of SDC to epithelia and membranes, which could be counteracted partly by PCs (Dial et al, 2008). The IC 50 values on MCF-7 cells of CUR-PC-SDC-MMs and free drug solution were 4.10 mg/ml and 6.93 mg/ml, respectively.…”
Section: Cell Toxicity Assaysmentioning
confidence: 87%
“…Bile salts are a class of surfactants that cause irritation and toxicity to the cell membrane. 25 Although some reports have shown that phospholipids can attenuate the toxicity of bile salts, 26,27 the toxicity of liposomes containing bile salts has not been evaluated in detail for ophthalmic drug delivery systems. Liposomes containing sodium deoxycholate showed greater toxicity in SDHCECs than the other liposomes.…”
Section: Cytotoxicitymentioning
confidence: 99%
“…However, some researches have shown that PL can reduce the noxiousness of bile salts (Dial et al, 2008). In this domain, Niu et al (2014) evaluated the cytotoxicity of BS-liposomes in concentration range of 0.25-6.25 mmol/L using cell growth inhibition assay employing Caco-2 cell monolayers.…”
Section: Cytotoxicity Of Bs-vesiclesmentioning
confidence: 99%